Channel planform dynamics using earth observations across Rel river, western India: A synergetic approach - Jodhani, Keval H.; Patel, Dhruvesh; Madhavan, N.; Soni, Utsav; Patel, Haard; Singh, Sudhir Kumar (Spatial information research (Online), 2024)
The complex channel planforms dynamics of river systems have attracted a lot of attention worldwide because of the tremendous effects that morphological changes have on nearby ecosystems and human populations. The present research aims at understanding intricate changes in the Rel river's channel as well as the erosion and deposition taking place over the past 48 years (1975–2023) through the application of Geographic Information System (GIS) and remote sensing. Spatial data within GIS were scrutinized to identify alterations in sinuosity, centreline migration, and large-scale dynamics of the river. A synergetic approach employing earth observation data, topographic mapping, and GIS processing, the research underscores the pivotal role of geospatial analysis in providing actionable spatiotemporal variations insights in the length of the river varying from 49.61 to 71 km, sinuosity index ranging from 1.25 to 1.79 and the maximum erosion and deposition were observed in year 1990 and 2015, respectively. This study's relevance extends to the broader context of river management and sustainable development, emphasizing the need for a holistic understanding of river systems to address contemporary challenges. In essence, the research contributes valuable insights for both scientific understanding and practical applications in the field of river dynamics, flood, drought, and environmental sustainability.